ABOUT THE DEVELOPMENT OF TOURISM IN OUR COUNTRY AND THE ACTIVITY OF TOURISM RESIDENTS - Khudoykulova Dilshoda Sharofiddin qizi (Scholar Express Journals, 2021)
This article is about the tourist attractions in Uzbekistan and the work being done there.
Keywords: Tourizm, monuments, ethno-tourism.